The securitization in the persian gulf and its changing dynamics - ÇAVUŞOĞLU, ESRA (My University, 2023)
The Persian Gulf has a very strategic importance in international politics because of its vast hydrocarbon energy resources and very strategic location as a transition point for international oil flow and trade. Therefore, regional security is a very significant issue not only in regional politics but also in global politics. However, the regional security map has not been designed by the regional actors and based on their own security interests and objectives but rather by global powers and based on their hegemonic interests and objectives. Since the end of the Second World War, in parallel with the Gulf States’ increasing importance based on their increasing oil-exporting and financial capacities, controlling regional security has become a very significant matter for the US-led Western hegemony. To control and design the security of the Persian Gulf, the US-led Western alliance established a security system in the region through cooperation with the regional allies, in different phases through the periods of changing regional geopolitics in each decade. The main argument of this article is that in the framework of this security system, the Gulf has been exposed to a constant securitization constructed based on politically defined security threats by the US policies at the expense of the regional stability and security and maintained through the armament of the Gulf States and military involvement of outsider powers. In the recent phase of the securitization in the “post-Counter Revolution” context, significant changes have emerged with the dynamics and the power balances of the regional security. This article aims to define these changes that challenge the Western-designed regional security architecture and to examine potency of the developments to result in desecuritization and normalization in long-term toward the stability of the region.

Basra Körfezi, sahip olduğu devasa hidrokarbon enerji kaynakları ve uluslararası petrol akışının ve ticaretin çok önemli bir geçiş noktası olan stratejik konumu sebebi ile uluslararası politikada çok stratejik bir öneme sahiptir. Bu nedenle bölgenin güvenliği yalnızca bölgesel siyasette değil, küresel siyasette de çok önemli bir konudur. Ancak, bölgesel güvenlik haritası, bölgesel aktörler tarafından ve kendi güvenlik çıkarları ve hedefleri esas alınarak değil, küresel güçler tarafından ve onların hegemonik çıkarları ve hedefleri doğrultusunda dizayn edilmektedir. İkinci Dünya Savaşı’nın sona ermesinden bu yana, Körfez ülkelerinin artan petrol ihraç ve finansal kapasitelerine bağlı olarak artan önemine paralel olarak, bölgesel güvenliğin kontrolü, ABD liderliğindeki Batı hegemonyası için çok önemli hale gelmiştir. ABD liderliğindeki Batı ittifakı, Basra Körfezi’nin güvenliğini mimarisini dizayn ve kontrol etmek için bölgesel jeopolitiğin değişme gösterdiği her on yıllık periyodlarda, bölgesel müttefiklerle işbirliği yaparak bölgede bir güvenlik sistemi kurmuştur. Bu makalenin ana argümanı, söz konusu güvenlik sistemi çerçevesinde Körfez’in, bölgesel güvenlik ve istikrar pahasına ABD politikaları tarafından siyasi olarak belirlenen tehdit tanımlamalarına dayalı olarak inşa edilen ve Körfez ülkelerinin silahlandırılması ve dış güçlerin askeri müdahalesi yoluyla sürdürülen sürekli bir güvenlikleştirmeye maruz kalmakta olduğudur. Güvenlikleştirmenin halen devam eden son aşamasında Arap Baharı karşı devrimi sonrası bağlamda, bölgesel güvenliğin dinamiklerinde ve bölgesel güç dengelerinde önemli değişimler ortaya çıkmıştır. Bu makale, Batı tarafından dizayn edilmiş bölgesel güvenlik mimarisine meydan okuyan bu değişimleri tanımlamak ve bu gelişmelerin bölgesel istikrarın sağlanmasınna yönelik olarak uzun vadede güvenlikleştirmenin iptaline ve normalleşmeye geçilmesine yol açma potansiyellerini incelemeyi amaçlamaktadır.
Basra Körfezi’nde güvenlikleştirme ve değişen dinamikleri
Keywords: Persian Gulf; Security; Securitization; Middle East; Basra Körfezi; Güvenlik; Güvenlikleştirme; Ortadoğu